2011
DOI: 10.1007/s12088-011-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Integrons from Escherichia coli Isolates Obtained from Some Selected Animals in Republic of Korea

Abstract: We detected integrons in 298 of 1106 Escherichia coli isolates obtained from the feces of pigs, chicken, ducks and elks. Among the sources there was higher number of integrons detected in the isolates of pigs. No integron was found in the isolates of gooses. Detection of lot of integrons in these isolates discovers the possibility of spread of antibiotic resistance genes in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(10 reference statements)
2
0
0
Order By: Relevance
“…While our study had the limitation of only detecting cassette regions under 4 Kb in size that had intact 5’ and 3’ ends, we still amplified integron cassettes from as many as 37.3% of isolates. Our detection of 340 (31%) class 1 integron containing strains and 44(4%) class 2 integron containing strains is comparable to data from studies using a similar methodology, which reported a prevalence of integrons to be above 30% [ 21 , 33 , 34 , 35 , 36 ]. Integrons are clearly widespread in faecal E .…”
Section: Discussionsupporting
confidence: 84%
“…While our study had the limitation of only detecting cassette regions under 4 Kb in size that had intact 5’ and 3’ ends, we still amplified integron cassettes from as many as 37.3% of isolates. Our detection of 340 (31%) class 1 integron containing strains and 44(4%) class 2 integron containing strains is comparable to data from studies using a similar methodology, which reported a prevalence of integrons to be above 30% [ 21 , 33 , 34 , 35 , 36 ]. Integrons are clearly widespread in faecal E .…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of intI 1 in cattle and buffalo was 95.65% and 100.0%, respectively and the prevalence of intI 2 for cattle and buffalo was 10.86% and 15.38%, respectively. The observations are comparable to the 50% in Australia (Barlow et al, 2004) but higher than 16.77 % from Korea (Hasan, 2010), 6% from Iran (Kheiri et al 2016). However higher percentage (84.5%) was reported by Ejaz et al (2021) from Brazil.…”
Section: Antimicrobial Susceptibility Testingsupporting
confidence: 66%